Study of dynamic reaction of tubulins in microtubules. A qm/mm simulation - Naghsh, Farnoush; Monajjemi, Majid; Zare, Karim (Nexo Revista Científica, 2020)
In this model one-dimensional microtubule is fixed at one of the two and simulated while the opposite end is allowed for growing in random situation. By this study at each step one tubulin has been added to the length for growing microtubule length. Computationally this can be done through generating a uniform random number between (0, 1). Microtubules are demonstrated as straight macromolecules consist of the linear chains of tubulin subunits in the length. QM/MM simulation has been applied to study dynamic instability of the microtubule length. It has been calculated a correct dimension around 10-6 meter of microtubules length consist of around 1650 tubulin dimers. Microtubule growth rate is related to the soluble tubulin dimer concentration and for all results shown here, simulation of any single condition was run 5–10 times.